First record of the genus Platerus Distant (Heteroptera: Reduviidae: Harpactorinae) from China, with the description of a third species of the genus - Zhao, Ping; Yang, Chun Wang; Cai, Wan Zhi (Zootaxa, 2006)
Platerus Distant, 1903 and Platerus pilcheri Distant, 1903 are reported for the first time from China. The female of Platerus pilcheri and Platerus tenuicorpus Zhao, Yang & Cai, sp. nov., is described and illustrated. A key to the three species of the genus is provided. The diagnostic characters of the genus are modified.